2014
DOI: 10.1111/1462-2920.12593
|View full text |Cite
|
Sign up to set email alerts
|

Temperature response of denitrification and anaerobic ammonium oxidation rates and microbial community structure in Arctic fjord sediments

Abstract: The temperature dependency of denitrification and anaerobic ammonium oxidation (anammox) rates from Arctic fjord sediments was investigated in a temperature gradient block incubator for temperatures ranging from -1 to 40°C. Community structure in intact sediments and slurry incubations was determined using Illumina SSU rRNA gene sequencing. The optimal temperature (Topt ) for denitrification was 25-27°C, whereas anammox rates were optimal at 12-17°C. Both denitrification and anammox exhibited temperature respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 67 publications
5
73
0
Order By: Relevance
“…Temperature block experiments have demonstrated that denitrification rates of Arctic-adapted microbes are highest at temperatures between 20 and 25 °C (ref. 17), but many other factors in situ can regulate the process. Thus, in the literature surveyed there is no clear temperature regulation of denitrification, anammox, or DNRA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature block experiments have demonstrated that denitrification rates of Arctic-adapted microbes are highest at temperatures between 20 and 25 °C (ref. 17), but many other factors in situ can regulate the process. Thus, in the literature surveyed there is no clear temperature regulation of denitrification, anammox, or DNRA.…”
Section: Discussionmentioning
confidence: 99%
“…NO 3 − concentrations often correlate positively with ra , although multiple environmental factors in concert, including sediment reactivity, can explain ra better than any one sole factor15. Temperature may also have a regulatory role for the two processes since the optimum temperature for polar-adapted denitrifying bacteria is 20–25 °C, while the optimum temperature for polar-adapted anammox bacteria is lower, at 9–12 °C (refs 16, 17). While these data suggest that anammox may have a competitive advantage in perennially cold Arctic sediments, results from temperature block experiments showed ra at 2.5 °C was only ∼22% (ref.…”
mentioning
confidence: 99%
“…The microbial process is regulated by various environmental factors, and many studies have reported the controlling factors of anammox bacterial abundance and activity, primarily including the temperature (Schubert et al 2006;Hou et al 2013;Zhao et al 2013;Canion et al 2014), water column NO 3 − /NO 2 − availability (Meyer et al 2005;Rich et al 2008;Nicholls and Trimmer 2009;Hou et al 2013), sediment organic carbon concentration (Dalsgaard and Thamdrup 2002;Trimmer et al 2003;Hu et al 2012a) and salinity (Dale et al 2009;Hou et al 2013;Sonthiphand et al 2014). In the current study, Pearson moment correlation analyses showed that both the activity and abundance of anammox bacteria significantly correlated with the soil ammonium concentration in the examined soil cores (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…S3). Over the past decade, multiple studies have investigated the effect of transiently or permanently low temperatures on the nitrification and denitrification of microbial community shifts in natural soil and aquatic environments [43,44]. Low temperatures reduced bacterial richness and enriched psychrotolerant species in engineering samples [45,46].…”
Section: Response Of Bacterial Community Composition To Short-term Tementioning
confidence: 99%